NUMBER OF TOTAL OVA AND EMBRYOS FROM FLUSHED DONOR COWS DEPENDING ON THE SKILLS OF TECHNICAL PERSONNEL - Grzeczka, Arkadiusz; Sobolewski, Jarosław (Translational Research in Veterinary Science, 2023)
One of the essential conditions for the successful acquisition of embryos is their perfect search. Experience of the person or team searching for the embryos seems to be of key importance in these cases. In commercial activities, we usually worked with one or two people with different qualifications. Their results in terms of the number of recovered embryos and oocytes (TOE) compared to ultrasound-detected corpora lutea were different. We therefore assumed that the success of an embryo search is critically dependent on the skill and experience of the person or embryo search team. The evaluation is based on results of embryo collection from 153 heifers and embryo donor cows. The donor was subjected to a standard procedure of superovulation with the use of FSH (Pluset Calier). On the 7th day after oestrus, the number of corpora lutea was counted in all females based on the ultrasound examination (iSkan Draminski), then the females were washed out. For this purpose, a Neustadt Aisch catheter was used (Minitübe). After sedimentation of the obtained fluid, embryosearch was performed under a stereoscopic microscope and magnification of 70X. Search was conducted by 11 teams – consisting of one or two people, differing in seniority and experience by comparing the values of Paerson correlation coefficients. Correlation coefficients R at P<0.05 were considered highly correlated, R values at P>0.05-0.065 were considered as showing a correlation trend, R values at P>0.065 were considered uncorrelated. The number of corpora lutea (NCL) averaged 9.83 whereas the number of embryos and oocytes – 6.03 (TRE). There was a clear relationship between the number of embryos and oocytes retrieved and the individuals or team searching for the embryos. This supports the thesis that the selection and training of embryo search technicians is critical to the success of the ET team. On the other hand, the discrepancies between the number of CL and TRE found in the ovaries could be due to the influence of other factors during the washout of the embryos.